The effects of ectomycorrhizal and saprotropic fungi on soil nitrogen mineralization differ from those of arbuscular and ericoid mycorrhizal fungi on the eastern Qinghai-Tibetan Plateau - Zhang, Miaomiao; Liu, Shun; Cao, Xiangwen; Chen, Miao; Chen, Jian; Xu, Gexi; Shi, Zuomin (Frontiers in Plant Science, 2023)
Interactions between soil fungi and soil environmental factors regulate soil nitrogen (N) mineralization rates on the eastern Qinghai-Tibetan Plateau. Some studies have also illuminated differences in soil N mineralization rate based on different mycorrhizal forests, but the associated effect of soil fungal functional guilds and soil environmental factors underlying this process are not well-understood. Three primary forests respectively dominated by Abies fargesii var. faxoniana (ectomycorrhizal, EcM), Cupressus chengiana (arbuscular mycorrhizal, AM) and Rhododendron phaeochrysum ectomycorrhizal (ericoid mycorrhizal, ErM) trees were selected in this area. Meanwhile, soil net N mineralization rate, soil fungal composition and soil enzyme activity among these three mycorrhizal forests were studied. Our results showed that there were significant differences in the seasonal variation of soil net N mineralization rates among three mycorrhizal forests. Soil net N mineralization rate in the AM forest was faster. EcM fungi and saprotroph are the main functional guilds in these three mycorrhizal forests. Meanwhile, the relative abundances of soil fungal functional guilds, soil temperature and soil peroxidase activity could explain 85.0% in the difference of soil net ammonification rate among three mycorrhizal forests. In addition, soil temperature, soil water-filled pore space and soil ammonium content play a central role in controlling the differing soil net nitrification rate among three mycorrhizal forests. Our results suggest differences in soil net mineralization among different mycorrhizal forest types are driven mainly by soil net ammonification. Soil fungal functional guilds and temperature regulate the rate of soil net ammonification by modulating soil peroxidase activity.